Conversion of Urea to Cyanamide Over Phosphorus-Modified H-ZSM-5 - Lu, Shuxiang; Wang, Longfu; Zhang, Yujian; Lu, Minghui; Zhi, Yahui; Tian, Yajie (Asian Journal of Chemistry, 2014)
A novel high active catalyst for the decomposition of urea into cyanamide was developed by treating H-ZSM-5 zeolite with phosphoric acid solution. The catalytic activity of the phosphorous modified H-ZSM-5 was tested in a continuous flow fixed bed reactor at 823 K and atmospheric pressure. The acidity of catalysts, especially Brønsted acid sites, is decreased by phosphorous modification. The selectivity for cyanamide of the catalysts is enhanced by the addition of phosphorus component. These results indicate that the Brønsted acid sites strength is a crucial factor for the selective production of cyanamide.